2014
DOI: 10.1016/j.jcm.2014.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Manual and Manipulative Therapy in the Perception of Pain and Cervical Motion in Patients With Tension-Type Headache: A Randomized, Controlled Clinical Trial

Abstract: Objective: The purpose of this study was to evaluate the efficacy of manipulative and manual therapy treatments with regard to pain perception and neck mobility in patients with tensiontype headache. Methods: A randomized clinical trial was conducted on 84 adults diagnosed with tension-type headache. Eighty-four subjects were enrolled in this study: 68 women and 16 men. Mean age was 39.76 years, ranging from 18 to 65 years. A total of 57.1% were diagnosed with chronic tension-type headache and 42.9% with tensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(8 citation statements)
references
References 24 publications
1
5
0
2
Order By: Relevance
“…Furthermore, there were no clear differences between the treatment arms during the 1 year follow-up regarding care seeking for their back/neck pain; the proportion that had not sought additional care the presiding three months at the 12 months follow-up was the same (61 %) in all three treatment arms. The findings from this study are similar to findings in some previous studies [ 5 , 30 , 31 ]. In a recent Cochrane systematic review Gross et al concluded that manipulation and mobilization provide similar effect for neck pain in mediate/short/intermediate-term follow-up [ 5 ].…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, there were no clear differences between the treatment arms during the 1 year follow-up regarding care seeking for their back/neck pain; the proportion that had not sought additional care the presiding three months at the 12 months follow-up was the same (61 %) in all three treatment arms. The findings from this study are similar to findings in some previous studies [ 5 , 30 , 31 ]. In a recent Cochrane systematic review Gross et al concluded that manipulation and mobilization provide similar effect for neck pain in mediate/short/intermediate-term follow-up [ 5 ].…”
Section: Discussionsupporting
confidence: 92%
“…One RCT had a low RoB for all methodological items, [21] 4 studies had 1 high RoB domain. [19–21,23] All studies had low risk in allocation concealment. [18–23] Three RCT had high risk for incomplete outcome data because some patients did not adhere to treatment for various reasons.…”
Section: Resultsmentioning
confidence: 99%
“…Screenings test cervical spine 42,71,[73][74][75]79 Abbreviations: CAS, color analog scale; DC/TMD, diagnostic criteria for temporomandibular disorders; GAD-7, generalised anxiety disorder scale; JFL, jaw functional limitation; MFIQ, mandibular function impairment questionnaire; PHQ, patient health questionnaire; PPT, pain pressure threshold; PPT, pressure pain threshold; TMJ, temporomandibular joint; TrP, trigger point; VAS, visual analog scale.…”
Section: Fonseca Anamnestic Index 60mentioning
confidence: 99%